2018
DOI: 10.1097/sla.0000000000002957
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Clinical Trial of Molecular Profiled Neoadjuvant Therapy for Localized Pancreatic Ductal Adenocarcinoma

Abstract: We report the first prospective clinical trial that utilized molecular profiling to select neoadjuvant therapy in patients with operable PDAC. Such high resectability rates have not been observed in prior neoadjuvant trials, suggesting that molecular profiling may improve the efficacy of chemotherapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…Regional nodal radiation was routinely included and typically involved the proximal celiac and superior mesenteric (artery and vein) vessels, along with the splenic or porta hepatis nodes depending on primary tumor location. A subset of patients with resectable PC received 2 months of chemotherapy on a clinical trial utilizing molecular profiling (16). For patients with BLR PC, neoadjuvant therapy consisted of a minimum of 2 months of chemotherapy followed by chemoradiation (50.4 Gy over 28 fractions).…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Regional nodal radiation was routinely included and typically involved the proximal celiac and superior mesenteric (artery and vein) vessels, along with the splenic or porta hepatis nodes depending on primary tumor location. A subset of patients with resectable PC received 2 months of chemotherapy on a clinical trial utilizing molecular profiling (16). For patients with BLR PC, neoadjuvant therapy consisted of a minimum of 2 months of chemotherapy followed by chemoradiation (50.4 Gy over 28 fractions).…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…18,19 Landry et al 20 These results are summarized in Table 1. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although these studies reported the survival outcome of an ITT cohort, none of them had a cohort treated by upfront surgery as a control. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Several meta-analyses investigated the efficacy of neoadjuvant.…”
Section: Pros Pec Tive S Tud Ie S and Me Ta-analys E Smentioning
confidence: 99%
“…36,37,[41][42][43][44] Considering recent progress in chemotherapy for UR PDAC, 45,46 a clinical question has been raised about the optimal protocol in the neoadjuvant setting. 24 Okano K 57 R, BR S1 + RT 91% N. R. N. R. 25 Motoi F 101 R, BR GEM/S1 73% 30.8 N. R. 26 Tsai S 130 R, BR FOLFIRINOX (n = 52) FOLFIRI (n = 26) GEM/Nab-P (n = 16) CAP/Nab-P (n = 15) *+RT (n = 83) 82% 38 45 27 Eguchi H 63 R GEM/S1 + RT 86% 55.3 NR 39,40 showed a significantly higher response rate and longer PFS than gemcitabine single-agent. 47 Ozaka et al 48 also reported similar results, with a high response rate and longer PFS, in a randomized, phase II trial.…”
Section: Op Timal Proto Col For Neoadj U Vant Ther Apymentioning
confidence: 99%
See 1 more Smart Citation
“…Using a panel of 6 protein biomarkers to guide gemcitabine or 5-FU based chemotherapeutic selection, the authors increased rates of treatment completion (neoadjuvant and resection) from 50 to 70% in borderline resectable PDAC cases, and from 80 to 90% in resectable cases. These improvements translated to overall survivals (OS) of 38 months in all patients and 45 months in patients who completed treatment, both an improvement over historical controls (4).…”
Section: Introductionmentioning
confidence: 99%